AB0514 Primary Disease of the Respiratory System in Patients with Systemic Lupus Erythematosus. (10th June 2014) - Borrell, H.; Narváez, J.; Armengol, E.; Zacarías, A.; Heredia, S.; Iriarte, A.; Roset, A.; Molina, M.; Juanola, X.; Capdevila, O.; Nolla, J.M.
Abstract : Objectives: To evaluate the frequency of the different types of primary diseases of the respiratory system in a group of patients with Sistemic Lupus Erytematosus (SLE). Methods: The target of the research were 243 patients with SLE who were assisted between 1980 and 2013 in a third level university hospital and they were registered in a specific data basis (Register AQUILES). There were chosen those patients with some kind of respiratory disease. Results: 49 (20%) patients were identified. The most frequent manifestation was the pleurisy, present in 39 patients (16%). Other manifestations were the interstitial lung disease (ILD) present in 5 patients (2.1%), acute lupus pneumonitis (ALP) in 4 (1.6%), pulmonary hypertension in 7 (3%), respiratory muscular illness (shrinking lung syndrome) in 2 (0.8%) and pulmonary thromboembolism in 2 (0.8%). In the cases of ILD, the average time of evolution from SLE diagnosis was of 9.4±6.7 years. In the 5 patients, all of them were women, ILD evolved with dry cough and insidious dyspnea. 3 of these patients were controlled with glucocorticoids; the other two also required cyclophosphamide, achieving to stop the evolution of the disease in 1 case, whereas the other patient died. The ALP cases appeared within the first two years of the SLE evolution. The average age of the 4 women suffering from ALP was 38±12 years. In them, the symptoms appeared intensely with fever, pleuritic pain in 50% of the cases, cough with occasional haemoptoic expectoration, dyspnea, diffuse pulmonary infiltrates in the chest X-ray and active alveolitis in the CT. All of them were treated with prednisone at doses of 1 mg/kg/day and one of them was also given bolus of metylprednisolona. In two of the patients an immunosuppressing treatment was added. The evolution was favourable in all the cases. In the comparative research with 194 controls with SLE without respiratory involvement significant differences were observed, being the patients with lung affection those who presented the highest frequency of pericarditis (p=0.0001) and the highest score in the harm index of SLICC/ACR (p=0.001). Conclusions: The pleural disease is the only primary disease of the respiratory system which is frequent in the SLE. The prevalence of the vascular lung disease, respiratory muscular disease, and of the different types of parenchymatous involvement is very low (≤3%). ALP is an early complication which usually takes place in the first years of the SLE evolution whereas ILD is a late complication. Both complications usually react to the treatment being the mortality rate low (11%). Neither the anti-Ro anti-bodies nor the anti-U1RNP seem to indentify the group of patients with the highest risk to develop these two complications. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5065